Interactional Metadiscourse in Students’ Abstracts across Studies at Universitas Qomaruddin - Eva Nur Mazidah; Lailatul Masruroh (Linguists : Journal Of Linguistics and Language Teaching, 2022)
Writing is one of the essential things that all students must do. In writing, the delivery of ideas needs to be arranged so that the writing is easy to understand and practical. One type of writing is when students write a research article for their final project or thesis. Abstract writing is one of the crucial sections of a final project or thesis because the abstract contains an outline of the research they did. In writing abstracts, metadiscourse markers were possible because they aimed to organize a sequence of ideas, attract readers' attention, and indicate how important the information was presented. This study investigated one hundred and twenty abstract theses from six study programs at Universitas Qomaruddin. They are English Department (PBI), Mathematic Department (PMT), Industrial Engineering (TI), Electrical Engineering (TE), Mechanical Engineering (MS), and Informatics Engineering (IF). Hyland (2005) formulated the interactional metadiscourse investigated as the primary reference. The results showed that all six study programs applied interactional metadiscourse markers when writing their abstracts. Moredespite different styles and preferences in applying markers. In terms of usage of overall metadiscourse, PBI applied the most markers, while MS applied the least. In terms of variants of metadiscourse, PBI also applied the most, and MS applied the least varied markers. The reasons behind more or less usage of interactional markers were influenced by how familiar they were with using English, as it also revealed their writing style. PBI is one example that their exposure to English pretty helps them vary the way they arrange their ideas in their abstracts. However, other surprising groups were PMT  and IF groups, which frequently showed the uses of metadiscourse markers. It also strengthened that English was not only dominated by English department students. It was more on how this language was known to many students at Universitas Qomaruddin. It is hoped that English as one of the international languages is no longer a big problem for students, especially in the case of abstract writing.